Pengaruh Modal Biaya Produksi Jumlah Tenaga Kerja dan Tingkat Pendidikan Terhadap Pendapatan UMKM Pada Industri Batu Bata Di Kecamatan Teras - Nisa amalia (Jurnal Manajemen Informatika & Teknologi, 2022)
Bricks are an important element in the construction of a building. In the sub-district of terraces, bricks are still done manually in the traditional way. The bricks themselves are part of MSMEs, therefore this study aims to determine how much influence the variables, capital, production costs, The number of workers, and the level of education on the income of MSMEs in Terrace District. The data used in this study are primary and secondary data. The analytical tool used is multiple linear regression analysis, with the results that the capital variable does not significantly affect the income of the brick MSMEs used. is in the Terrace sub-district, the production cost variable has a significant positive effect on the income of the brick SMEs in the Teras sub-district, the variable number of workers has a significant positive effect on the brick MSME income in the Terrace sub-district and the education level variable has no significant effect t to the income of brick SMEs in Teras District.